Development of transfer measurement standards in the form of high-purity metals - L. A. Konopelko; P. V. Migal; E. P. Sobina (Стандартные образцы)
The article studies the development of transfer measurement standards in the form of high-purity metals (Ag, Cd, Co, Cr, Cu, Fe, Ge, Mn, Mo, Ni, Pb, V, Zn). The evaluation of the mass fraction of the main component (MDOK) is performed by an indirect method (100 %o minus the sum of impurities). The impurity composition of the reference measurement standard materials was determined by mass spectrometry with inductively coupled plasma, reductive and oxidative melting using the State primary measurement standard of mass (molar) fraction and mass (molar) concentration of the component in liquid and solid substances and materials, based on coulometry, GET 176. The relative expanded uncertainty of MDOK (k = 2, P = 0,95) in the reference measurement standards was less, than 0,01 %o, in gravimetrically prepared solutions of the reference measurement standard it was less than 0,05 %o in most cases. The solutions of the reference measurement standards were used in the determination of certified values of metal mass fraction and mass concentration in reference materials for composition of mono-element solutions of approved types. The relative expanded uncertainty of certified values (k = 2, P = 0,95) of reference materials variedfrom 0,22 %o to 0,54 %o. Thus, it was demonstrated that metals can be used as reference measurement standards for storing a unit of the mass fraction of the main component and transferring it during characterization of reference materials for composition of solutions of the corresponding chemical elements. This work was performed within the research project «Research in the field of measurements of physicochemical composition and properties of substances, aimed at the development of State transfer measurement standards in the form of high-purity substances for reproduction and transfer of the units, characterizing chemical composition of solid substances» under the code «Purity» (2015-2017) and research and development project «Research in the field of measurements ofphysicochemical composition and properties of substances, aimed at the development of State transfer measurement standards in the form of high-purity substances for reproduction and transfer of the units, characterizing the chemical composition of solid substances and the development of reference measurement procedures» under the code «Purity-2» in the field of physicochemical measurements of composition and properties of inorganic components in solid substances (metals and salts) and food safety indicators under the code «Purity-2b» (2017-2019).